Autoimmune hepatitis in patients with human immunodeficiency virus infection: A systematic review of the published literature. Issue 37 (September 2019) - Mubder, Mohamad; Azab, Mohamed; Jayaraj, Mahendran; Cross, Chad; Lankarani, Daisy; Dhindsa, Banreet; Pan, Jen-Jung; Ohning, Gordon
Abstract: Background: Liver disease in patients with HIV is common and typically has complex and multifactorial presentations that represent a major cause of morbidity and mortality. Autoimmune hepatitis (AIH) is rarely reported in patient with HIV and the disease course and clinical outcomes for treatment have not been well characterized. We are aiming to determine the patient characteristics, disease prevalence, and treatment outcomes from published articles of patients with HIV and AIH. Method: A systematic search of PubMed, Web of Science, and Google Scholar through February 20 th, 2019 identified 15 studies that reported the outcomes of AIH in patients with HIV. Because of the small sample sizes and skewed distributions, resampling tests of mean differences using permutation distributions (MAXn = 10, 000 permutations) were utilized; analyses were performed using R (v. 3.5.1). Categorical differences were calculated using Fisher exact test for odds ratio = 1 (equal odds), and Cramer V was calculated for effect size; analyses were completed in SPSS (v. 25). Results: By reviewing 15 studies reporting a total of 35 patients with AIH and HIV, male patients were found to have significantly higher aspartate transaminase and alanine transaminase levels at time of diagnosis. No other significant findings identified. The CD4 count and viral load did not show significant correlation with AIH diagnosis or its prognosis. All patients but one who presented with severe immune deficiency and responded to highly active anti-retroviral therapy received immunosuppressive treatment without side effects and achieved remission except 2 lost to follow-up and 3 expired. Conclusion: Although rare, but AIH can develop in patients with HIV and physicians should consider it in the differential diagnosis for HIV patients presented with abnormal liver function tests, especially after excluding hepatitis C virus and drug-induced liver injury. Patients with immune deficiency disorders who present with AIH can be treated safely with steroid either as monotherapy or in combination with another immune suppressant therapy.